Globalization and Multiproduct Firms - Volker Nocke; Stephen Yeaple (University of Mannheim, Department of Economics, 2013)
We present an international trade model with multiproduct firms. Firms are heterogeneously endowed with two types of capabilities that jointly determine the trade-off within firms between managing a large portfolio of products and producing at low marginal cost. The model can explain many of the documented cross- sectional correlations in firm performance measures, including why larger firms are more productive and more diversified, and yet more diversified firms trade at a discount. Globalization is shown to induce heterogeneous responses across firms in terms of scope and productivity, some of which are consistent with existing empirical work, while others are potentially testable.
urn:nbn:de:bsz:180-madoc-339850
Keywords: F12; F15; 330; multiproduct firms; trade liberalization; diversification discount; firm heterogeneity; productivity